Learning focuses: Its validation through a questionnaire (Research, Society and Development, 2024)
The objective of this article is to bring the results of a questionnaire validation process designed to reveal evidence of the presence of the Learning Focuses on the answers provided by participants in scientific events. The preparation of the questionnaire began with a survey of the productions published regarding Learning Focuses, which provided us with a period from 2012, the first publication identified, to 2021, when we ended the searches. To interpret the twenty-eight selected articles, we used the methodological procedures indicated by Content Analysis, looking for the expressions used to characterize the Focuses. Such expressions were organized into emerging categories, represented by words or phrases, which later formed five distinct questionnaires, one for each Focus: Interest, Knowledge, Reflection, Community, and Identity. The questionnaire was validated through Exploratory Factor Analysis based on the answers given by 188 participants, resulting in five factors, which demonstrated high factor loadings associated with the corresponding items, aligning with the theory of the respective Learning Focuses. The results indicate that the questionnaire presents exploratory evidence of validity and an adequate internal structure to assess the presence of Learning Focuses. Each Focus can be described by specific indicators based on scientific productions related to the topic. Consequently, the developed instrument offers a viable alternative to the semi-structured interview to assess the presence of Focuses on scientific events.